Bibliometric Analysis of Research on Civil Servants with Disability in Indonesia - Ni Putu Diah Ratih Nareswari Putri (Journal of Social Research, 2025)
Including people with disabilities in public service is crucial to Indonesia's commitment to the Sustainable Development Goals (SDGs). Despite the special recruitment program introduced in 2017 to hire civil servants with disabilities, research on the integration of these individuals into public sector management remains limited. This study aims to conduct a bibliometric analysis of research on civil servants with disabilities in Indonesia from 2012 to 2025. The research employed VOS viewer to analyze 197 articles from Google Scholar and Scopus, focusing on the field's evolution, key themes, and research trends. The findings reveal a positive growth trend in related publications, particularly in disability, accessibility, and civil service, yet indicate a lack of research on internal civil service management systems for disabled individuals. Most studies have focused on inclusive public service delivery but neglected topics such as recruitment, career progression, performance evaluation, and institutional support for civil servants with disabilities. The study calls for further research on these under-explored areas to strengthen disability-inclusive governance and improve human resource management systems. These findings can help inform the development of policies and frameworks for integrating disabled individuals into the public sector effectively.